“It is in the Nature of Men”: The Normalization of Non-Consensual Sex and Intimate Partner Violence Against Women with Acquired Physical Disabilities in South Africa - Hunt, Xanthe (Violence against women, 2024)
This study employed a cross-sectional, qualitative individual interview methodology to explore South African women with physical disabilities’ experiences of intimate partner and sexual violence, inclusive of non-consensual and coerced sexual intercourse. For the participants, disability was a factor that intersected with gender norms to create vulnerability to abuse, and that patriarchal ideologies constructing how women should perform their gendered roles in marriage or sexual partnerships, as well as disability stigma, exacerbated this vulnerability. It is important to develop understandings of the different risk factors for violence – at the individual level and in the context of dyadic relationships – to develop programming to better support women.